Entre faíscas e fuligens: a trajetória social das queimadas nos canaviais paulistas - Sabadin, Ana Carina (2024)
This thesis aims to interpret the social trajectory of burning in sugarcane fields, to find a specific path that leads to the erasure of a debate that has been going on for decades in the context of São Paulo. Our hypothesis is that this trajectory does not lead to a concrete obliteration of the flames – and gradually, in the course of our analysis, we noticed that this concrete goes beyond the materialization of these flames. The context in which this thesis was born was marked by the elimination – or significant reduction – of burning and the advance of mechanized sugarcane cutting. In general terms, burning is the use of fire to strip the sugarcane plant so that it can be cut more efficiently by hand. Eliminating burning thus meant eliminating the use of fire and the manual labor of sugarcane cutters – two of the fuels that cause tension in disputes and conflicts, which, during the promotion of ethanol fuel in the early 2000s, began to damage the image of the sector. The São Paulo Agri-Environmental Protocol, signed in 2007, thus dissipates soot from the sugarcane fields, boosting the mechanization of cutting raw sugarcane and legitimizing the sector’s “good environmental practices”. In the wake of this Protocol, the emergence of conflagrations sheds light on fire as a detriment, something uncontrolled, destructive, and not in the interests of this sector, challenging these “good practices” and demanding strategies to combat the flames and the image they convey. This emergency leads us to question the trajectory mentioned above, contributing to the construction of our hypothesis. Far from this emergence already seeming to point to the concrete non-erasure of the flames in the sugarcane fields, it was only the surface of what this thesis is based on: thermopolitics, a form of power that is still capable of encompassing the logic of capital accumulation, advancing into the concrete and symbolic of social relations. The reach of this thermopolitics is made possible by the trajectories that make up the social trajectory of these burnings. Beyond extinguishing the flames, we go through the trajectories of lighting up, oscillating, and igniting. From a methodological point of view, we took a qualitative approach, based on bibliographical and documentary research, semi-structured interviews with representatives of different segments of the sector, the collection of secondary numerical data, as well as the observation of debates promoted in lives attended by representatives of São Paulo’s public authorities and the sector. The investigation focuses on the administrative region of Ribeirão Preto, listed as the empirical universe.